2017
DOI: 10.1111/ajt.14166
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Promote Bronchial Epithelial Cell Secretion of Matrix Metalloproteinase-9 via a C-C Chemokine Receptor Type 2 Pathway: Implications for Chronic Lung Allograft Dysfunction

Abstract: Chronic lung allograft dysfunction (CLAD) is the major limitation of long-term survival after lung transplantation. CLAD manifests as bronchiolitis obliterans syndrome (BOS) or restrictive allograft syndrome (RAS). Alloimmune reactions and epithelial-to-mesenchymal transition have been suggested in BOS. However, little is known regarding the role of allogenicity in epithelial cell differentiation. Primary human bronchial epithelial cells (BECs) were treated with activated T cells in the presence or absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…Conversely, the neutrophilic proteotype was associated with the upregulation of proteins secreted by neutrophils (azurocidin, S100, annexin A, neutrophil gelatinase-associated lipocalin, myeloperoxidase) (80). Interestingly, in a hypothesis-based approach, Barbaro et al detected the exhaled matrix metalloprotease-9 (MMP9) in different phenotypes of asthma and found it elevated in severe neutrophilic asthma (89), echoing the results of both the aforementioned study by Schofield et al, where MMP9 was associated with neutrophilic inflammation in bronchial mucosa from asthmatic patients (86), and those of a previous study in the field of lung transplantation that showed that the serum MMP9 level was predictive of bronchiolitis obliterans syndrome in lung transplant recipients, a condition also related to airway neutrophilia and bronchial remodeling (90).…”
Section: From Phenotypes To Endotypes Using Unbiased Proteomic/metabosupporting
confidence: 75%
“…Conversely, the neutrophilic proteotype was associated with the upregulation of proteins secreted by neutrophils (azurocidin, S100, annexin A, neutrophil gelatinase-associated lipocalin, myeloperoxidase) (80). Interestingly, in a hypothesis-based approach, Barbaro et al detected the exhaled matrix metalloprotease-9 (MMP9) in different phenotypes of asthma and found it elevated in severe neutrophilic asthma (89), echoing the results of both the aforementioned study by Schofield et al, where MMP9 was associated with neutrophilic inflammation in bronchial mucosa from asthmatic patients (86), and those of a previous study in the field of lung transplantation that showed that the serum MMP9 level was predictive of bronchiolitis obliterans syndrome in lung transplant recipients, a condition also related to airway neutrophilia and bronchial remodeling (90).…”
Section: From Phenotypes To Endotypes Using Unbiased Proteomic/metabosupporting
confidence: 75%
“…Recent literature highlighted the major role of AEC in the remodeling processes associated with chronic diseases, infections or transplantation [ 1 ]. Although modulation of TGF-β induced remodeling by inflammatory environment has been described [ 14 16 ], the direct interaction between TGF-β and TLR signaling in AEC remains unexplored. AEC were cultured with low dose of TGF-β (1 ng/ml) to emphasize the synergy with TLR3 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…AEC were isolated and cultured as already described [ 16 ]. Briefly, human primary BEC were obtained from lung donor trachea or bronchi, included within the multicentre COLT (Cohort in Lung Transplantation, NCT00980967) study (Comité de Protection des Personnes Ouest 1-Tours, 2009-A00036–51).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…162 CCL2 also supports TGF-β-induced matrix metallopeptidase 9 (MMP-9) production by airway epithelial cells, which is important to fibroplasia and remodeling. 163 However, the pathogenesis of CLAD is considerably more complex than what can be explained by the simple Th1/Th2 paradigm.…”
Section: Effector and Regulatory Immune Responses To Injury And Theirmentioning
confidence: 99%